Theology in a postmodern culture: ten challenges - Rossouw, G. J. (Hervormde teologiese studies, 1993)
The shift from a modem to a postmodern cuhure which is still in the making brings a new understanding of self and the world with it. Theology therefore has to reflect on the implications and compatibility of this new understanding of the self and the world for a Christian understanding of reality as revealed in the Bible and other relevant texts. In this paper I shall describe some dimensions of this cultural shift that is occurring and then reflect on the challenges and opportunities that they offer to theologians. The dimensions of the postmodern culture discussed in the paper are the broader notion of rationality that the postmodern culture proposes, its broader anthropology, the emphasis on the involvement of both expertise and experience in decisionmaking, and finally the reduction of the world to a ‘global village’.